2012
DOI: 10.1007/s00417-012-1935-6
|View full text |Cite
|
Sign up to set email alerts
|

Paracentral retinal holes occurring after macular surgery: incidence, clinical features, and evolution

Abstract: In summary, paracentral MHs are uncommon complications which can occur at the site where ILM peeling has been initiated or completed. Except for the closest holes to fovea, they have good visual prognosis and do not require any treatment underlining the importance of initiating the ILM peeling as far as possible from the fovea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 26 publications
2
48
1
Order By: Relevance
“…The most plausible mechanism could be the iatrogenic trauma, which may occur during surgery when grasping the ILM with forceps [1]. ILM peeling may induce surgical trauma of the underlying nerve fiber layer and Müller cells, causing secondary delayed degeneration of the adjacent retinal neurons [1, 3, 9]. Ultrastructural studies have shown remnants of Müller cell processes attached to the removed ILM with signs of necrosis [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most plausible mechanism could be the iatrogenic trauma, which may occur during surgery when grasping the ILM with forceps [1]. ILM peeling may induce surgical trauma of the underlying nerve fiber layer and Müller cells, causing secondary delayed degeneration of the adjacent retinal neurons [1, 3, 9]. Ultrastructural studies have shown remnants of Müller cell processes attached to the removed ILM with signs of necrosis [3].…”
Section: Discussionmentioning
confidence: 99%
“…ILM peeling may induce surgical trauma of the underlying nerve fiber layer and Müller cells, causing secondary delayed degeneration of the adjacent retinal neurons [1, 3, 9]. Ultrastructural studies have shown remnants of Müller cell processes attached to the removed ILM with signs of necrosis [3]. However, in the majority of published cases there was no retinal whitening or retinal hemorrhages consistent with postoperative trauma [1, 3, 10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations